2021
DOI: 10.1016/j.ijid.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Sudden Unexpected Community Deaths in Lusaka, Zambia, Africa - A Medico-Legal Whole-Body Autopsy Case Series

Abstract: Background Data from Africa of sudden and unexpected COVID-19 community deaths, and underlying pathological, demographic and co-morbidity features require definition. Methods We performed a descriptive case series of COVID-19 related deaths seen at Forensic Post-Mortem autopsy examination of sudden and unexpected Community Deaths in Lusaka, Zambia, Africa. Post-Mortem gross and histopathological examinations of all organs were performed according to Standard Operating P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
0
16
0
1
Order By: Relevance
“…After excluding duplicates and preliminary screening, 155 full-text articles were assessed for eligibility, and 141 studies were excluded for not meeting the inclusion criteria, leaving 13 studies fulfilling the inclusion criteria ( Figure 1 , Supplementary File 2 ). 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19
Figure 1 Flow diagram of selected studies for the meta-analysis according to the PRISMA. PRISMA = Preferred Reporting Items for Systematic Reviews and Meta-Analyses.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After excluding duplicates and preliminary screening, 155 full-text articles were assessed for eligibility, and 141 studies were excluded for not meeting the inclusion criteria, leaving 13 studies fulfilling the inclusion criteria ( Figure 1 , Supplementary File 2 ). 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19
Figure 1 Flow diagram of selected studies for the meta-analysis according to the PRISMA. PRISMA = Preferred Reporting Items for Systematic Reviews and Meta-Analyses.
…”
Section: Resultsmentioning
confidence: 99%
“…At autopsy, histopathologic findings of deep vein thrombosis were observed in 16.6% of cases in 4 studies (mean age 56.0 years). 7 , 9 , 14 , 17 The administration of anticoagulant treatment was not systematically performed in the reviewed studies. Quality assessment showed that all studies were of moderate-high quality according to the Newcastle-Ottawa quality assessment scale ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that individuals with co-morbidities are at increased risk of severe COVID-19 disease and death (Dustan, 1990;Edler et al, 2020;Mucheleng'anga et al, 2021;Mwananyanda et al, 2021). In other studies, risk of infection in HIV-positives or in previous TB patients was not more than 1.5-2 times higher than for HIV-negatives or non-TB patients (Chanda D et al;Mulenga et al, 2021).…”
Section: Associated Risk Factorsmentioning
confidence: 99%